2019
DOI: 10.1186/s12885-019-5684-3
|View full text |Cite
|
Sign up to set email alerts
|

The primary lesion apparent diffusion coefficient is a prognostic factor for locoregionally advanced nasopharyngeal carcinoma: a retrospective study

Abstract: Background To explore prognostic value of the pre-treatment primary lesion apparent diffusion coefficient (ADC) in locoregionally advanced nasopharyngeal carcinoma (LA-NPC). Methods A total of 843 patients with newly diagnosed LA-NPC were enrolled from January 2011 to April 2014 and divided into two groups based on ADC values: the low-ADC group and high-ADC group. The 3-year local relapse-free survival (LRFS), distant metastasis free survival (DMFS), disease-free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
3
10
1
Order By: Relevance
“…In addition, lower pretreatment ADC values showed an association with better long-term prognostic indicators of patients with NPC in a recent study. 19 Consistent with our results, 2 studies found no significant difference between the pretreatment average ADC values of the primary NPC tumors that showed good and poor response to treatment; however, they used other DWI parameters to differentiate the local tumor response, namely, ADC changes and ADC skewness. 6,24 In contrast, Yan et al 8 revealed that patients with NPC who demonstrated higher pretreatment ADC values of the primary tumor had higher locoregional control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, lower pretreatment ADC values showed an association with better long-term prognostic indicators of patients with NPC in a recent study. 19 Consistent with our results, 2 studies found no significant difference between the pretreatment average ADC values of the primary NPC tumors that showed good and poor response to treatment; however, they used other DWI parameters to differentiate the local tumor response, namely, ADC changes and ADC skewness. 6,24 In contrast, Yan et al 8 revealed that patients with NPC who demonstrated higher pretreatment ADC values of the primary tumor had higher locoregional control.…”
Section: Discussionsupporting
confidence: 91%
“…6,18,19 The ADC value derived from DWI represents factors that affect water diffusion, especially cellular density. 6,19 Tumors with low ADC values have higher cellularity with more viable and metabolically active tumor tissue and are more likely to respond to treatment including radiotherapy and chemotherapy, which destroy cancer cells by causing damage and lysis of the proliferating cells. 18,20 Conversely, tumors with high ADC values, which indicate lower cellularity and less metabolically active tissue, are likely to result in hypoxia and thus demonstrate a poorer response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study include the small number of patients and the diversity of the tumor locations and histology as well as the MRI equipment used and technical parameters, such as magnetic field (1.5 and 3 T), DW sequences (EPI and TSE DWI), and TR/TE have great influence on the ADC values 16,17 . ADC values have been reported to vary by histological type in head and neck malignancies 18‐21 although there was no difference between histology and subsite in this study. Thus, the ratio of ADC values in regions of skull base invasion/main tumor was also calculated in this study.…”
Section: Discussionmentioning
confidence: 73%
“…The potential of ADC in therapy assessment and prognosis prediction of NPC has been reported earlier (20,21,(26)(27)(28)(29)(30)(31). Several previous studies have shown that primary tumors with lower baseline ADC values had a better response to chemoradiotherapy as compared to those with higher baseline ADC values for NPC (32,33).…”
Section: Discussionmentioning
confidence: 73%